Effectiveness of osteopathic craniosacral techniques: a meta-analysis - Amendolara, Alfred; Sheppert, Alexander; Powers, Ryan; Payne, Andrew; Stacey, Stephen; Sant, David (Frontiers in Medicine, 2024)
Background: Craniosacral osteopathic manipulative medicine-also known as craniosacral therapy (CST)-is a widely taught and used component of osteopathic medicine. This paper seeks to systematically review and conduct a meta-analysis of randomized controlled trials assessing the clinical effectiveness of CST compared to standard care, sham treatment, or no treatment in adults and children.Methods: A search of Embase, PubMed, and Scopus was conducted on 10/29/2023 and updated on 5/8/2024. There was no restriction placed on the date of publication. A Google Scholar search was conducted to capture grey literature. Backward citation searching was also implemented. All randomized controlled trials employing CST for any clinical outcome were included. Studies not available in English as well as studies that did not report adequate data were excluded. Multiple reviewers were used to assess for inclusions, disagreements were settled by consensus. PRISMA guidelines were followed in the reporting of this meta-analysis. Cochrane's Risk of Bias 2 tool was used to assess for risk of bias. All data were extracted by multiple independent observers. Effect sizes were calculated using a Hedge's G value (standardized mean difference) and aggregated using random effects models. The GRADE system was used to assess quality of evidence.Results: The primary study outcome was the effectiveness of CST for selected outcomes as applied to non-healthy adults or children and measured by standardized mean difference effect size. Twenty-four RCTs were included in the final meta-analysis with a total of 1,613 participants. When subgroup analyses were performed by primary outcome only, no significant effects were found. When secondary outcomes were included in subgroup analyses, results showed that only Neonate health, structure (g = 0.66, 95% CI [0.30; 1.02], Prediction Interval [-0.73; 2.05]) and Pain, chronic somatic (g = 0.34, 95% CI [0.18; 0.50], Prediction Interval [-0.41; 1.09]) show reliable, statistically significant effect. However, these should not be interpreted as positive results as wide prediction intervals, high bias, and statistical limitations temper the real-world implications of this finding.Conclusions and Relevance: CST demonstrated no significant effects in this metaanalysis, indicating a lack of usefulness in patient care for any of the studied indications.